Timing of the last deglaciation in Belarus - RINTERKNECHT, VINCENT R.; PAVLOVSKAYA, IRINA E.; CLARK, PETER U.; RAISBECK, GRANT M.; YIOU, FRANCOISE; BROOK, EDWARD J. (Boreas, 2007)
We measured 10Be concentrations in boulders collected from the Orsha and Braslav moraines, associated with the Last Glacial Maximum extent and a recessional stage of the Scandinavian Ice Sheet (SIS), respectively, providing a direct dating of the southeastern sector of the ice‐sheet margin in Belarus. By combining these data with selected existing radiocarbon ages, we developed a chronology for the last deglaciation of Belarus. The northeastern part of the country remained ice free until at least 19.2 ± 0.2 cal. kyr BP, whereas the northwestern part of the country was ice free until 22.3 ± 1.5 cal. kyr BP. A lobate ice margin subsequently advanced to its maximum extent and deposited the Orsha Moraine. The ice margin retreated from this moraine at 17.7 ± 2.0 10Be kyr to a position in the northern part of the country, where it deposited the Braslav Moraine. Subsequent ice‐margin retreat from that moraine at 13.1 ± 0.5 10Be kyr represented the final deglaciation of Belarus. Direct dating of these moraines better constrains the relation of ice‐margin positions in Belarus to those in adjacent countries as well as the SIS response to climate change.